Neurostimulation and Neuromodulation in Contemporary Therapeutic Practice - Larrivee, Denis; Mansoor Rayegani, Seyed (IntechOpen, 2020)
Clinical applications of neurostimulation or neuromodulation are experiencing rapid growth, driven by an evolution in neurotechnologies, the limitations of pharmacotherapy, and an improving understanding of brain physiology. New methods are promising for intractable or marginally tractable cognitive diseases and for adjunct therapies, as they offer greatly improved spatial and temporal resolution, thereby promising greater specificity and quicker recovery from disease. This book includes up-to-date and in-depth studies of many of these therapies, with chapters addressing their use in epilepsy, spasticity, pain, neurodegeneration, and spinal cord dysfunctions, among others, illustrating their versatility and therapeutic promise for cognitive dysfunction.